Virtual training basics - Huggett, Cindy (ASTD training basics series., 2018)
It's a digital world; is your training up to speed? Build your virtual training skills with this new edition of Virtual Training Basics by Cindy Huggett. You don't have to be a tech wizard to follow her tested and proven techniques for enhancing your virtual training design and delivery. E-learning has been around since the late 90s, but it continually evolves. Sometimes, it may seem impossible to keep up--but your learners need courses that they can take anywhere, organizations need to save money and time on travel, and everyone expects your material to be as current as possible. Take it back to the basics. Virtual Training Basics will get you started with the fundamentals of virtual training, and then build you up through design and facilitation, with updated material and two new chapters to cover the latest breakthroughs and skills you need to know. In this book, you will: · Get tips from a variety of seasoned virtual trainers. · Gain insight into the differences (and similarities) between facilitating in-person training and virtual training. · Understand the fundamentals of virtual training design. Whether you're new to virtual training or looking for ways to update your existing skills, Virtual Training Basics, 2nd edition, will take you there.